Genetic mapping of quantitative trait loci (QTLs) with effects on resistance to flower bud thrips (megalurothrips sjostedti) identified in recombinant inbred lines of cowpea (Vigna unguiculata (L.) Walp) - Omo-Ikerodah, E.E.; Fawole, I.; Fatokun, C.A. (2008)
The first major insect pest of cowpea at reproductive stage is the flower bud thrips (FTh), which, if not controlled, is capable of causing significant grain yield reduction. Breeding for resistance to FTh in cowpea has been hindered by the quantitative nature of the resistance, and the breakdown of resistance under high insect infestation. The purpose of this study was to use molecular markers to identify genetic loci associated with the expression of resistance to FTh. A set of 92 recombinant inbred lines (RILs) was generated from a cross between susceptible and resistant lines. One hundred and thirty nine markers [134 Amplified Fragment Length Polymorphism (AFLP) and 5 cowpea derived microsatellites] were used to construct a linkage map using this set of RILs. The linkage map spans 1620 cM of the cowpea genome and markers were distributed in 11 linkage groups. Average distance between adjacent markers was 9.6 cM. There were significant associations between 23 DNA markers and resistance to flower bud thrips (P<0.05) using single marker analysis. QTLs with effects on resistance were detected in five linkage groups. The QTL on linkage group 3 explained 32.0% of the variation for resistance while all the five QTLs together explained 77.5%.